Switching Intention of Electric Vehicle in Indonesia - Kurniawan, Hendra; Suntono, Annita Rosliana; Sudrajat, Darjat (Jurnal Locus Penelitian dan Pengabdian, 2025)
The transition from fossil fuel vehicles to electric vehicles (EVs) in Indonesia is critical for reducing emissions and achieving sustainable transportation. Despite government support through policies like Presidential Regulation No. 55/2019, EV adoption remains low due to challenges such as high costs, limited infrastructure, and consumer hesitancy. This study investigates the factors influencing switching intentions to EVs in Indonesia, employing the push-pull-mooring (PPM) framework to analyze environmental concern, cost concern, perceived usefulness, financial incentives, and infrastructure readiness. Using a mixed-methods approach, the research collected data from 136 respondents in Greater Jakarta through structured questionnaires, analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings revealed that environmental concern, cost concern, and perceived usefulness significantly positively influence switching intentions, while financial incentives showed limited impact. Surprisingly, infrastructure readiness did not significantly moderate these relationships, suggesting other barriers may hinder adoption. The study contributes theoretically by adapting the PPM model to EV adoption, identifying cost concern as a push factor and financial incentives as a pull factor. Practically, it highlights the need for targeted policies, such as enhanced public awareness campaigns and improved charging infrastructure, to accelerate EV uptake. Future research should explore additional moderators like socio-cultural influences and adopt longitudinal designs to track evolving consumer behavior. This research provides valuable insights for policymakers, industry stakeholders, and researchers aiming to foster EV adoption in emerging markets like Indonesia.